POTENTIAL KETAPANG (Terminalia cattapa) LEAF EXTRACT AS A DOXORUBICIN CO-CHEMOTHERAPY AGENT ON BREAST (T47D) AND CERVIX (HeLa) CANCER CELL LINES - Sundhani, Elza; Solehah, Senja Nur; Septiadi, Binaripan; Nurulita, Nunuk Aries (Universitas Muhammadiyah Magelang, 2024)
Doxorubicin (DOX) is chemotherapy for breast and cervical cancer with serious side effects. Ketapang (Terminalia cattapa) is a potential plant as a co-chemotherapy agent. The purpose of this research was to examine the sensitivity of DOX as a cytotoxicity drug in combination with ethanolic extracts of ketapang leaves (EKL) against T47D and HeLa cancer cells. Cytotoxicity was determined using the MTT assay, with DOX concentration series (0.625-40 nM for T47D and 0.5-6 M for HeLa) and EKL (50-1000 mg/mL) used in combination with the study. DOX and EKL combination assays utilizing their respective IC50 values were performed in T47D cells and HeLa cells, and the results were used to calculate the Combination Index (CI). Furthermore, the doubling time method was used to investigate the combination of DOX and EKL proliferation inhibition on both cell lines. DOX and EKL had IC50 values of 158 nM and 30 mg/mL for T47D, respectively, and 3.4 M and 640 mg/mL for HeLa cell growth. While DOX and EKL have a synergistic effect on T47D cells, their combined effect on HeLa cells is cytotoxic and dose-dependent. EKL increases the inhibitory effect of DOX on the proliferation of T47D and HeLa cancer cells. In T47D cells, the combination of DOX and EKL has a higher potential for cytotoxic and antiproliferative activity than in HeLa cells